EVALUASI PRODUK PEMBELAJARAN MULTIMEDIA (PELIN) EVALUATION OF LEARNING MULTIMEDIA PRODUCT (PELIN) - Jihadil Qudsi S.; Anthony Anggrawan (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2016)
This paper purpose is to discover shortcomings of multimedia product of Pelin and to conduct a survey to users of multimedia Pelin . Pelin is an online e-learning multimedia for students of Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Bumigora Mataram, which is able the students to upload task file and download learning material. Pelin system is based on restful webservice that can provide distant learning. There are four levels of evaluation, those are reaction, learning, behavior and result. The formative evaluations result show: the Pelin multimedia disadvantages are: not supports interactive face to face learning, not facilitates audio communication, not be fully user friendly, could not upload graphic and image files, not be provided by feedback facility of test result and also not have help menus. The summative evaluation result found that the Pelin Multimedia is supports independent learning, provides web-client application, improves reaction of student to learn, increases student knowledge comprehension, increases learning behavior, and gives good learning result. Statistical comparison tests found there are significant differences influence the implementation of Pelin and there is no difference in terms of the level of reaction, learning and behavior towards the use of Pelin for S1 and D3 students.